New Insights on Respiratory Syncytial Virus Prevention - Edyta Kopera; Hanna Czajka; Paweł Zapolnik; Artur Mazur (Vaccines, 2023)
Respiratory syncytial virus (RSV) is a well-known infant pathogen transmitted mainly by droplets. It is a leading cause of upper respiratory tract infections in children, usually with a mild course of illness. RSV has also been a threat to older people, especially those with underlying medical conditions. For a long time, prevention was limited to passive immunoprophylaxis with palivizumab for high-risk infants. There was a strong need to find other treatment or prevention methods against RSV infections. In addition, after the coronavirus disease 2019 (COVID-19) pandemic, some significant changes in RSV epidemiology have been observed. Researchers noticed the shift in RSV seasonality and age distribution and the increased number of cases in older infants and adults. All of these made the need to find other medical options even stronger. Fortunately, two protein-based vaccines against RSV have successfully passed all phases of clinical trials and have been approved for use by adults and older people. One of them is also approved for infants from birth to 6 months of age (after maternal immunisation during pregnancy) and for pregnant women between 24 and 36 weeks of pregnancy. Also, a new passive immunisation option named nirsevimab (a highly potent monoclonal antibody with a long half-life) is now available for the paediatric group. In this review, we will discuss the previous and current RSV prevention methods in the light of structural discoveries of RSV antigens.